Vocal delivery quality in earnings conference calls - Baik, Bok; Kim, Alex G.; Kim, David S.; Yoon, Sangwon (Journal of Accounting and Economics, 2025)
We study the economic consequences of managers’ vocal delivery quality during earnings conference calls. We introduce a novel measure, vocal delivery quality, that captures the acoustic comprehensibility of audio information for an average listener. Our measure relies on a deep-learning algorithm applied to a large sample of earnings call audio files. Consistent with predictions from the psychology and accounting literatures, we find evidence that the quality of managers’ vocal delivery deteriorates when they deliver negative news, such as a decrease in earnings or negative narrative information, and positive but transitory earnings news. We show that the stock market reacts in real time to managers’ vocal delivery quality. We also document that the vocal delivery quality has an effect on information intermediaries such as analysts and the media. Overall, our findings underscore the role of vocal dimensions in corporate oral disclosures.